THE SOCIO-ECONOMIC SITUATION IN TURKESTAN AFTER THE OCTOBER REVOLUTION AND ITS CONSEQUENCES (International Congress on Economics, Management and Business Studies, 2026)
This article examines the socio-economic situation in Turkestan following the October Revolution of 1917 and analyzes its major consequences. The establishment of Bolshevik rule led to political instability, economic decline, food shortages, changes in property relations, and a deterioration in the living standards of the population. The exclusion of local representatives from governing institutions and the neglect of the national, religious, and social interests of the indigenous population intensified public dissatisfaction. The article also highlights the suppression of the Turkestan Autonomy and the growing resistance to Soviet authority. These developments demonstrate that the new political system failed to gain broad support among the local population and further deepened the existing socio-economic problems in the region.
Keywords: Turkestan, October Revolution, Bolshevik government, socio-economic situation, economic decline, food shortage, Turkestan Autonomy, Soviet authority, local population, political resistance.